PERSPEKTIF MAHASISWA PRODI PAI TENTANG MATA KULIAH PENGEMBANGAN KURIKULUM DALAM MENYIAPKAN CALON PENDIDIK DI UIN SUNAN KALIJAGA YOGYAKARTA - Desi Dwi Maheningsih, Sabarudin, Mohamad Agung Rokhimawan (CV. ADIBA AISHA AMIRA, 2024)
This research aims to understand the perspective of Islamic Religious Education (PAI) students towards the Curriculum Development course and their role in preparing prospective educators at UIN Sunan Kalijaga Yogyakarta. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews, observation and document analysis. The research results show that the majority of students consider the Curriculum Development course to be very important in equipping them with the knowledge and skills needed as prospective educators. However, there are several challenges faced in the learning process, such as students' lack of knowledge in compiling articles about curriculum themes that have been shared in class, less varied teaching methods and a lack of in-depth practice on certain materials that need to be covered thoroughly until students understand.